2022
DOI: 10.1186/s41937-021-00082-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 vaccines on economic activity

Abstract: This paper empirically examines the economic effects of COVID-19 vaccine rollouts using a cross-country daily database of vaccinations and high-frequency indicators of economic activity—nitrogen dioxide (NO2) emissions, carbon monoxide (CO) emissions, and Google mobility indices—for a sample of 46 countries over the period December 16, 2020 to June 20, 2021. Using surprises in vaccines administered, we find that an unexpected increase in vaccination per capita is associated with a significant increase in econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…As a series of publications shows, while government containment measures have been quite effective in flattening the “pandemic curve,” their side effect has been to severely depress economic performance and employment [ 17 , 18 ]. A recent study, using a sample of 46 countries for the first half of 2021, finds that an increase in vaccination per capita is associated with a significant increase in economic activity [ 19 ]. They also find economic benefits being larger when vaccination rates are higher.…”
Section: Resultsmentioning
confidence: 99%
“…As a series of publications shows, while government containment measures have been quite effective in flattening the “pandemic curve,” their side effect has been to severely depress economic performance and employment [ 17 , 18 ]. A recent study, using a sample of 46 countries for the first half of 2021, finds that an increase in vaccination per capita is associated with a significant increase in economic activity [ 19 ]. They also find economic benefits being larger when vaccination rates are higher.…”
Section: Resultsmentioning
confidence: 99%
“…However, even when most countries have begun distributing vaccines and treatments, the number of confirmed cases of COVID-19 is still not decreasing. This is because vaccinations lead to unexpected increase in human mobility so that the rate of COVID-19 transmission is still sustained or even increased ( Deb et al, 2022 ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors found no evidence of the effects of the vaccine rollout on healthcare and employment. In addition, Deb et al ( 2022 ), using cross-country data covering 46 countries over the period December 2020–June 2021, found evidence that an increase in vaccination per capita is associated with a significant increase in economic activities, such as nitrogen dioxide and carbon monoxide emissions and recreation mobility. In a related development, Deb et al ( 2022 ), using cross-country data covering 17 countries, showed that vaccine deployment has persistent positive effects on the level of economic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Deb et al ( 2022 ), using cross-country data covering 46 countries over the period December 2020–June 2021, found evidence that an increase in vaccination per capita is associated with a significant increase in economic activities, such as nitrogen dioxide and carbon monoxide emissions and recreation mobility. In a related development, Deb et al ( 2022 ), using cross-country data covering 17 countries, showed that vaccine deployment has persistent positive effects on the level of economic activity. Finally, Agarwal and Gopinath using a cost–benefit analysis, found that vaccinating 40 percent of the world's population by 2021 could cost around $50 billion, while benefits could reach about $9 trillion in economic gains.…”
Section: Introductionmentioning
confidence: 99%